2018
DOI: 10.1136/bcr-2018-224856
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral chorea/ballismus: detection and management of a rare complication of non-ketotic hyperglycaemia

Abstract: Non-ketotic hyperglycaemia (NKH) is the most common metabolic cause of hemichorea-hemiballismus (HC-HB) and an often-reversible condition. A 68-year-old man presented to the emergency department with a severe hyperglycaemic episode and altered mental status. He was treated appropriately and discharged home after his blood glucose levels were normal with an improvement of mental status. Four weeks after the discharge, he returned with flailing movements of bilateral upper and lower limbs. MRI of the brain revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Many variations of this presentation have been described, including bilateral MRI changes [ 15 16 17 18 19 20 21 22 23 24 ], ipsilateral MRI changes [ 25 ], bilateral chorea [ 23 26 ], recurrent chorea [ 27 28 ] and persistent chorea [ 25 29 30 ]. Cases have been described in the pediatric population [ 31 32 33 34 35 36 ] as well as in both children and adults presenting with ketotic hyperglycemia [ 22 37 38 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many variations of this presentation have been described, including bilateral MRI changes [ 15 16 17 18 19 20 21 22 23 24 ], ipsilateral MRI changes [ 25 ], bilateral chorea [ 23 26 ], recurrent chorea [ 27 28 ] and persistent chorea [ 25 29 30 ]. Cases have been described in the pediatric population [ 31 32 33 34 35 36 ] as well as in both children and adults presenting with ketotic hyperglycemia [ 22 37 38 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…She had increased T1 signal in her left putamen and HbA 1c of 8.9% (74mmol/mol) 18 . The other cases had recent significant hyperglycaemia with blood glucose of 64.4mmol/L (case A) 19 and 54.6mmol/L (case B) 20 treated with intravenous insulin followed by subcutaneous switch on discharge. The cases presented with hemiballismus at four and 12 weeks post‐discharge, respectively, in the setting of euglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…There are only three other case reports of diabetes‐related hemiballismus in the setting of euglycaemia. They all describe improved glycaemic control at presentation in the setting of recent suboptimal glycaemia 18–20 . One case had a previous stroke (which is itself a risk factor for hemiballismus) and only mild hyperglycaemia of 11–14mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Besides an abnormal metabolic panel, it is associated with noticeable changes in neuroimaging. CT and MRI scans of several affected patients show hyperdensities and hyperintense signals respectively on the contralateral striatum (7). A meta-analysis of 53 cases conducted by Oh et al showed that 89% of the cases had hemichorea with contralateral putaminal hyperintensity and 11% had generalised chorea with bilateral putaminal changes on MRI(8).…”
Section: Discussionmentioning
confidence: 99%